2020
DOI: 10.2147/cmar.s245697
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hepatic Arterial Infusion Combined with Systemic Chemotherapy for Patients with Extensive Liver Metastases from Gastric Cancer</p>

Abstract: Purpose: Liver metastases in patients with gastric cancer often indicate poor prognosis. Once liver metastases are extensive, it is difficult to achieve disease control by using systemic chemotherapy alone. The purpose of this study was to evaluate the effect and safety of hepatic arterial infusion (HAI) combined with systemic chemotherapy on extensive liver metastases from gastric cancer. Patients and Methods: Between 2012 and 2019, 21 patients with extensive liver metastases from gastric cancer (LMGC) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…None of the patients experienced grade 4 adverse effects. Grade 3 toxic effects included bone marrow suppression (14.3%) and diarrhea (9.5%) (30). A study of Western patients showed that seven patients received HAIC with a median duration of six cycles.…”
Section: Hepatic Arterial Infusion Chemotherapy (A B)mentioning
confidence: 99%
“…None of the patients experienced grade 4 adverse effects. Grade 3 toxic effects included bone marrow suppression (14.3%) and diarrhea (9.5%) (30). A study of Western patients showed that seven patients received HAIC with a median duration of six cycles.…”
Section: Hepatic Arterial Infusion Chemotherapy (A B)mentioning
confidence: 99%